The Effect of Locus of Control and Self-Efficacy on Employee Performance Mediated by Organizational Citizenship Behavior (OCB) (Case Study of Employees of PT BPR BKK Purwodadi (Perseroda) - Widi Raharjo; Lie Liana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of locus of control and self-efficacy on employee performance, mediated by organizational citizenship behavior (OCB). The population in this study was 332 employees of PT BPR BKK Purwodadi (Perseroda). The number of samples used was 113, taken using the Roscoe formula (1975). The sampling technique used purposive sampling with the criteria of more than 1 year of service and employees in the marketing department. Data processing was used SPSS software version 22. Data analysis techniques included respondent descriptions, variable descriptions, validity tests, reliability tests, F tests, R2 tests and hypothesis tests (t tests). Mediation tests used path analysis. The results showed that locus of control had a positive and significant effect on OCB. Self-efficacy had a positive and significant effect on OCB. Locus of control had a positive and significant effect on employee performance. Self-efficacy had a positive and significant effect on employee performance. OCB had a positive and significant effect on employee performance. OCB mediates the influence of locus of control and self-efficacy on employee performance.